1988
DOI: 10.1002/joc.3370080603
|View full text |Cite
|
Sign up to set email alerts
|

The southern oscillation and South African summer rainfall

Abstract: Using data since 1882 the relationship between summer rainfall over South Africa and the ENSO phenomenon is investigated. A strong association between Warm Events and dry spells, and between Cold Events and wet spells is discussed. The temporal and spatial variability in the relationship is presented. Rainfall during December and March correlates significantly with the previous winter's SO1 but rainfall during the mid-summer months, January and February, shows much weaker correlation. A significant relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 16 publications
1
39
0
1
Order By: Relevance
“…From the GCM, the leading empirical orthogonal function of Indian Ocean SSTs accounts for 39% of the total variance in NDJ rainfall in southern Africa. The seasonal changes in predictability appear to be consistent with the findings of Lindesay (1988) andvan Heerden et al (1988) for South Africa. ENSO-rainfall relationships for South Africa are stronger during December to March than the early part of the rainy season.…”
Section: Discussionsupporting
confidence: 83%
“…From the GCM, the leading empirical orthogonal function of Indian Ocean SSTs accounts for 39% of the total variance in NDJ rainfall in southern Africa. The seasonal changes in predictability appear to be consistent with the findings of Lindesay (1988) andvan Heerden et al (1988) for South Africa. ENSO-rainfall relationships for South Africa are stronger during December to March than the early part of the rainy season.…”
Section: Discussionsupporting
confidence: 83%
“…The influence of ENSO events is strongest during the summer rainfall months of December to March when the El Niño/La Niña events have reached maturity (Mason and Jury, 1997). Van Heerden et al (1988) found a strong relationship between summer monthly SOI values and corresponding summer monthly rainfall in South Africa. These findings make it likely that there exists a simultaneous, non-lagged relationship between the ENSO and rainfall in Southern Africa (Hydén and Sekoli, 2000).…”
Section: The Southern Oscillation and Summer Rainfallmentioning
confidence: 76%
“…(e.g. Lindesay et al, 1986;Lindesay, 1988;Van Heerden et al, 1988;Jury et al, 1994;Mason, 2001) and that ENSO warm events [negative values of the Southern Oscillation Index (SOI)] are frequently associated with less than average rainfall and drought over much of southern Africa (e.g. Tyson, 1986;Ropelewski and Halpert, 1987;Janowiak, 1988;Van Heerden et al, 1988;Mason and Jury, 1997).…”
Section: The Southern Oscillation and Summer Rainfallmentioning
confidence: 99%
“…In particular, much attention has been focused on the ENSO-rainfall relationship over the domain of South Africa (Dyer, 1979;Lindesay, 1986Lindesay, , 1988Harrison, 1986;Van Heerden et al, 1988;Matarira, 1990;Lindesay and Vogel, 1990;Walker, 1990;Mason and Lindesay, 1993;Jury et al, 194J4). It was found that the Southern Oscillation Index (SOT) indicates a positive simultaneous correlation with 1996, Meteorological Society of Japan rainfall during the southern summer months, while the strongest correlations are found during December and January (Lindesay, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the ENSOSouth African rainfall association is modulated with the phase of the Quasi-Biennial Oscillation (Mason and Lindesay, 1993). The continental circulation pattern linking the warm ENSO event and reduced South African rainfall is characterized by respective positive and negative pressure anomalies almost throughout the troposphere over the southern African subcontinent and regions southward (Wright, 1977;Van Loon and Madden, 1981;Pan and Oort, 1983;Van Loon and Shea, 1985;Lindesay, 1986;Van Heerden et al, 1988;Matarira, 1990). That is, an enhanced poleward pressure gradient.…”
Section: Introductionmentioning
confidence: 99%